The Use of Information and Communication Technology (ICT) Amongst EFL Teachers: Perceptions and Challenges - Asnawi Muslem; Rena Juliana (English Education Journal, 2017)
The purpose of this research was to investigate the perceptions and challenges of English teachers to the implementation of Information and Communication Technology (ICT) in ELT classrooms. The objectives of this study were to find out their perception of ICT and the challenges they face when using it. This study used mixed methods, qualitative and quantitative in nature. Purposive sampling was used to select the subjects of this study who were 26 English teachers at senior state high schools in Banda Aceh. The instruments used to collect data were a questionnaire and interviews. The data was analyzed and interpreted through qualitative and quantitative procedures. The results showed that these English teachers agreed that ICT was very helpful in teaching. However, limited time and insufficient equipment coupled with poor internet connections as well as a lack of knowledge and experience and lack of ICT training became obstacles that the teachers face in using ICT. Through this study, the teachers are expected to further deepen their knowledge of ICT so as to improve their skills in teaching English using ICT.